Critical Analysis of High School Students' Metacognitive Awareness of Physics Using Rasch Modeling - Ahmad Fahrudin; Eka Maryam; Astri Riance; Moh. Irma Sukarelawan; Pujianti Bejahida Donuata (Indonesian Review of Physics, 2025)
.